Analisis Volatilitas Dan Forecast Saham PT. Antam (Persero) Tbk dan PtT.Adaro Energy Tbk dengan Garch, Egarch dan Gjr - Yasir Maulana (ECONBANK: Journal of Economics and Banking, 2020)
An extraordinary event that causes shock can affect volatility which causes asymmetric variance and error or commonly called asimetric shock / effect. This paper aims to analyze the volatility of stock returns of PT ANTAM (Persero) Tbk and PT Adaro Energy Tbk in the period of 2008 to 2016. The research results show that ANTM and ADRO have a GARCH effect and also have a leverage effect where the optimal model is found in the GJR model (0,1,1) for ANTM and GJR (1,1,1) for ADRO. Forecasting results shows that ADRO has higher volatility but in a relatively low percentage of volatility about 0.001 while ANTM have a tendency to decrease volatility with a fairly large percentage of volatility about 0.0025